Empowering refugee families in transit: the development of a culturally competent and compassionate training and support package - Papadopoulos, Irena; Lazzarino, Runa; Sakellaraki, Ourania; Dadãu, Victor; Apostolara, Paraskevi; Kuckert-Wöstheinrich, Andrea; Mauceri, Manuela; Kouta, Christiana (My University, 2021)
Background: Refugee parents who fled conflicts suffered violence and traumas and face huge challenges in supporting the health and welfare of their children while in transit. Aims: To describe the development of a culturally competent and compassionate training and support package (TSP) for nurses, social and health care workers and volunteers, with a focus on parenting needs among unsettled refugees fleeing conflict. Methods: The multi-method approach included: a scoping review covering parenting needs of refugees fleeing conflict zones; collection of stories from refugee parents, healthcare workers and volunteers via a mobile application; discussions between team members; a piloted and evaluated curriculum. Results: High levels of family distress and deterioration of parental identity were identified. Informed by these results, the curriculum is articulated along 20 bite-sized learning units, covering four age stages of childhood as well as targeting adults’ well-being. Pilot training was evaluated positively, confirming feasibility and usefulness of the TSP. Conclusions: Unsettled refugee parents fleeing conflicts face psycho-social and practical difficulties negatively affecting their parenting skills. The care workforce should be trained in order to provide culturally competent and compassionate support to help these families. Open access digital platforms are promising as autodidactic and self-help tools among hard-to-reach populations.
Keywords: Culture; Compassionate care; Parenting/families; Public and patient involvment; Italy; Romania; Mental health; Mobility; Multi-methods; Practice development; Violence